PSYCHIATRIC COMORBIDY IN PATIENTS SUFFERING FROM CHRONIC MEDICAL DISEASES - Faraj, Siba Sameer; Mohammad Amin, Nazar Mohammad; Abdulkareem, Makwan Mohammed (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2024)
Psychiatric symptoms are commonly distributed among general population and commonly comorbid with chronic medical diseases such as diabetes and thyroid diseases. This study aimed at discussing common mental health problems that are comorbid with chronic medical diseases in a single short paper by using different recent sources and references. This review article was conducted by using different recently published articles considering common mental health issues that are comorbid with chronic medical diseases such as diabetes mellitus, ischemic heart diseases, and thyroid diseases. Anxiety symptoms, depression, insomnia and somatization are commonly present among patients who have diabetes mellitus, thyroid disorders, hypertension, ischemic heart diseases, peptic ulcer and rheumatic illnesses.